Palma, forjador de la identidad cultural iqueña - Vásquez Peña, José (2018)
This work illustrates the extent to which the work of Ricardo Palma, set in Ica, has been developing, over the course of time, the iqueñidad as a feeling and passion for the terroir. It is established how this identity process that begins in the first decades of the 20th century, parallel to the forging of Peruvianness, the supreme objective of Palma, achieves the birth and strengthening of the iqueñidad, which in the current time is expressed in a formidable explosion of elements that allow to verify that the cultural management, the artistic creation, the educational management, and others have associated themselves with the urgent need to strengthen Ica’s cultural identity.